САДОВИТЕ ВО МАКЕДОНСКИТЕ ЦРКОВНОСЛОВЕНСКИ ТЕКСТОВИ КАКО ДЕЛ ОД МАТЕРИЈАЛНАТА КУЛТУРА (Филолошке студије, 2019)
A wide range of lexemes, which name different dishes, are found in Macedonian Church Slavonic texts: oil cups, clayey and metal pots, dishes for wine, sinks and wide dishes. The researches have shown that there are numbers of lexemes that show the specific meaning of the dish connected to its usage. These names of dishes have been researched in this addition. Also, names of dishes, that have rare and limited usage in the texts, are mentioned in the addition. During the research, we used materials from the data of The Dictionary of the Macedonian Recension of Church Slavonic, which is being done at the Institution of Macedonian Language „Krste Misirkov“, Skopje.